2001
DOI: 10.1054/bjoc.2000.1577
|View full text |Cite
|
Sign up to set email alerts
|

Absence of rearrangements in the BRCA2 gene in human cancers

Abstract: Summary Mutations of BRCA2 in sporadic breast and ovarian carcinomas are exceedingly rare. This led to the suggestion that large genomic rearrangements could be involved. We performed Southern blots in genomic DNA from 130 primary breast cancers and 83 cancer cell lines (breast, ovarian, pancreatic and small cell lung carcinomas) and found no genomic rearrangements. These results suggest that a gene other than BRCA2 is the target of the frequent 13q12.3 allelic deletions in human cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This study concluded that large rearrangements in BRCA1 are uncommon in breast cancer. No rearrangements were identified in the BRCA2 gene by Southern blot analysis of 130 primary breast cancers and 83 cancer cell lines [Chin et al, 2001].…”
Section: Rearrangements Identified In Sporadic Tumorsmentioning
confidence: 98%
“…This study concluded that large rearrangements in BRCA1 are uncommon in breast cancer. No rearrangements were identified in the BRCA2 gene by Southern blot analysis of 130 primary breast cancers and 83 cancer cell lines [Chin et al, 2001].…”
Section: Rearrangements Identified In Sporadic Tumorsmentioning
confidence: 98%
“…Until recently, only two genomic rearrangements had been identified in six studies that analyzed hereditary breast cancer patients or primary breast tumors among diverse European populations ( Peelen et al , 2000 ; Lahti-Domenici et al , 2001 ; Chin et al , 2001 ; Wang et al , 2001 ; Gad et al , 2002 ; Bunyan et al , 2004 ). The greatly reduced incidence of large genomic alterations that affect BRCA2 compared to BRCA1 most likely reflects differences in the density of Alu repeat sequences at the two loci, and these initial studies were not very supportive of the inclusion of this type of analysis in routine mutation testing of HBOC families ( Preisler-Adams et al , 2006 ).…”
Section: Brca2 Rearrangementsmentioning
confidence: 99%